Theriogenology 2017
DOI: 10.5772/intechopen.69549
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin in Reproductive Seasonality in Buffaloes

Abstract: Buffaloes are characterized by seasonal reproductive activity. Anestrus buffalo heifers and lactating buffaloes were used to study the effect of melatonin treatment on the resumption of ovarian activity during out-of-breeding season. Buffaloes of treated group were injected or implanted with melatonin (18 mg melatonin/50 kg body weight). Using CIDR-eCG protocol preceded with melatonin successfully achieved estrus behavior and induced conception rate during out-of-breeding season. Furthermore, the reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…A previous study has shown seasonal variation in protein contents in buffaloes where highest crude protein contents were observed in winter and vice versa (Ahmad et al, 2013). This could be due to lower concentration of prolactin in summer and shorter daylight, both of which leads to higher melatonin level (Ramadan, 2017). In our study, we also found higher casein level in BuMEC after melatonin treatment.…”
Section: Discussionsupporting
confidence: 59%
“…A previous study has shown seasonal variation in protein contents in buffaloes where highest crude protein contents were observed in winter and vice versa (Ahmad et al, 2013). This could be due to lower concentration of prolactin in summer and shorter daylight, both of which leads to higher melatonin level (Ramadan, 2017). In our study, we also found higher casein level in BuMEC after melatonin treatment.…”
Section: Discussionsupporting
confidence: 59%
“…Problems such as hyperprolactinemia (reduction of pulsatile gonadotrophin secretion) are caused by the direct effect of stress and adverse environmental factors on the neuroendocrine configuration. Similarly in cattle, the estrous cycle of the buffalo is divided into four periods, pro-estrus, estrus, metaestrus and diestrous (Ramadan, 2017). Note.…”
Section: Female Buffalomentioning
confidence: 99%
“…These hormones are regulated by the hypothalamic-pituitary and gonadal axis (Bhimte et al, 2021). The level of circulating reproductive hormones affects the reproductive performance of cattle and buffaloes (Ramadan, 2017). The regulation and secretory pattern of these hormones are affected by different disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%